IMPROVING STUDENTS’ LISTENING SKILL BY USING SONGS’ LYRICS A STUDY CONDUCTED AT SMAN 1 MELONGUANE - Richi Teppa; Rinny Rorimpandey; Jenie Posumah (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The purpose of the study was to find out whether the used of songs’ lyrics could improve the students’ listening skill. The subjects of this research were the third grade in the A class consisted of 25 students. This research was quantitative research through pre-experimental design with pretest and posttest. Prior to treatment, the students were given a pre-test. The post-test was given to students after they had received treatment or had used the lyrics of songs to improve their listening skills. The result of this research shows that the mean score of the posttest was higher (8,08) and pretest (6,36). It means that the used of songs’ lyrics were effective to improving students’ listening skill. Results of the data analysis indicated that students’ performance in listening comprehension were better than before. As in the posttest result the students’ score and abilities were increased. This research is still far from perfection, however by doing so, it is believed that students will obtain a higher level of achievement or outcome in English class, and English teachers will be encouraged to employ this strategy to improve students' listening skills.